Investigating the effect of thickness profile of a rotating functionally graded disc on its creep behavior. (May 2013) - Dwivedi, Dharmpal D; Gupta, Vinay K; Dham, Ashok K
Creep behavior of rotating discs made of functionally graded materials with linearly varying thickness has been investigated. The discs contain silicon carbide particles in a matrix of pure aluminum. The effect of varying disc thickness gradient (TG) has been investigated on the stresses and strain rates in the composite disc. The study shows that with the increase in disc TG, the radial, tangential and effective stresses decrease throughout the disc. The strain rates in the disc also reduce significantly with the increase in TG of the disc.